Heat Loss Analysis of Continuous Drying Oven with Outside Conveyor Chain - Jitwiriya, Weerayut; Chantrasmi, Tonkid; Nontakaew, Udomkiat; Yongyingsakthavorn, Pisit (Applied Science and Engineering Progress, 2021)
In continuous manufacturing lines, conveyor chains are employed to transport future products in and out of these ovens in various processes of the production. As such, the typically metal conveyor system creates a significant heat loss by absorbing the thermal energy from inside the oven and releasing it outside. This work analyzed heat transfer of a novel drying oven design with their conveyor chains outside of the heated zone. The problem was complex due to multiple modes of heat transfer and an intermediate area between the heated zone and the outside chain. A mathematical model was proposed along with a numerical solution approach based on Finite Difference Method (FDM). Using problem parameters from a real latex-gloves production line as an example, it was found that the new design could reduce the heat loss by 23.1% when replacing all conventional ovens with the new designs.